Predictive influence of locus of control on adult learners’ academic attitude and engagement - Itasanmi, Sunday Abidemi; Ajani, Oluwatoyin Ayodele; Mabayoje, Dahunsi Emmanuel; Odiaka, Stella Ifeyinwa (Nurture, 2023)
Purpose: The primary purpose of this study was to empirically examine the predictive influence of locus of control (internal and external) on adult learners’ academic attitude and engagement using the theory of andragogy. Design/Methodology/Approach: The study adopted a quantitative research approach and data were collected from 216 adult learners participating in literacy programmes in Oyo State, Southwest Nigeria. The study's data collection tool was a structured questionnaire that focused on four domains: demographic parameters, locus of control (internal and external), academic attitude and academic engagement. A partial Least Square-Structural Equation Modelling (PLS-SEM) analysis with SmartPLS software was used to analyze the collected data. Findings: The findings of the study indicated that adult learners' academic attitude significantly influenced their academic engagement. It was revealed that the internal locus of control had a significant positive impact on the academic attitude and engagement of the adult learners. Furthermore, the relationship between academic attitude and engagement was moderated by internal locus of control. However, the external locus of control had no significant effect on the academic attitude and engagement of adult learners. Conclusion: Interventions aimed at improving adult learners' academic attitude and engagement should take into account the role of the internal locus of control. Strategies such as goal-setting and self-reflection critical to developing a stronger internal locus of control may be effective in promoting positive academic attitudes and engagement among adult learners. Practical Implications: This study’s results have implications for both literacy organizers and facilitators regarding support strategies to maximize learners’ engagement, motivation and effective learning.